2015
DOI: 10.3389/fnmol.2015.00009
|View full text |Cite
|
Sign up to set email alerts
|

A network of RNA and protein interactions in Fronto Temporal Dementia

Abstract: Frontotemporal dementia (FTD) is a neurodegenerative disorder characterized by degeneration of the fronto temporal lobes and abnormal protein inclusions. It exhibits a broad clinicopathological spectrum and has been linked to mutations in seven different genes. We will provide a picture, which connects the products of these genes, albeit diverse in nature and function, in a network. Despite the paucity of information available for some of these genes, we believe that RNA processing and post-transcriptional reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 345 publications
(405 reference statements)
0
20
0
1
Order By: Relevance
“…PPA can be further divided into two main subtypes, semantic variant (svPPA) and non-fluent variant (nfvPPA) [4]. Moreover, (CHMP2B) [5] and, recently, TANK-binding kinase 1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…PPA can be further divided into two main subtypes, semantic variant (svPPA) and non-fluent variant (nfvPPA) [4]. Moreover, (CHMP2B) [5] and, recently, TANK-binding kinase 1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, administration of PGRN was suggested as a therapy for AD, based on an inverse dose-dependent relation of PGRN with amyloid load mediated via a PGRNrelated loss of phagocytosis function of the microglial cells [10]. Besides studies into PGRN's pathological mechanism [11], blood and cerebrospinal fluid (CSF) levels of PGRN are extensively studied as markers of FTD, since low blood PGRN levels were found to predict mutations in the PGRN-gene with high sensitivity [12][13][14][15][16][17][18]. Moreover, PGRN is studied as a blood marker for cancer [19] and metabolic disorder pathologies [20].…”
Section: Introductionmentioning
confidence: 99%
“…One of these is miRNA-9; its expression has been found to be reduced in induced-pluripotent-stem-cell-derived neurons of FTD-patients with TDP-43 mutations [56]. TDP-43 is responsible for stabilizing GRN-RNA [57]. On the other hand, and similarly to miRNA-132, in epilepsy (animal model and human) miRNA-9 has shown to be elevated, possibly being proepiletogenic through inhibiting the NFkB1 -transcript and therefore increasing inflammation [58] as well as increasing migration [59].…”
Section: Progranulin and Micrornamentioning
confidence: 99%